2018
DOI: 10.29252/qums.12.6.29
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sleep Quality with Depression in Patient with Acute Myocardial Infarction

Abstract: Background and Objectives: Depression is one of the most psychological outcomes in patients with acute myocardial infraction, which can affect the sleep quality in these patients. Given that adequate sleep has important effect on heart function, the present study was conducted with the aim of determining the correlation between sleep quality with death and cardiac depression in patient with acute myocardial infarction (AMI). Methods: In this descriptive-correlational study, 407 patients with acute myocardial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Only one of them [24] reported that 3–5-year-old children in kindergartens were significantly more infected than those in the other age groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one of them [24] reported that 3–5-year-old children in kindergartens were significantly more infected than those in the other age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Study type was specified in 15 articles, all of which were cross-sectional. Diagnostic methods included the Scotch tape technique in 17 papers [ 10 12 , 17 – 24 , 26 , 28 – 32 ] and Formalin ether in two papers [ 25 , 27 ]. Of these studies, 15 were performed among preschoolers or kindergarteners [ 10 12 , 17 – 24 , 28 – 31 ], while four studies [ 25 – 27 , 32 ] investigated the infection prevalence among primary school children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show that patients suffer from sleep disorders (SD) after heart accidents and coronary artery surgery [ 1 ]. Sleep is an important modulator of heart function and can thus lead to lower activity and cardiac load, so that SDs such as insomnia and hypersomnia have also been considered important factors in the pathogenesis and progression of cardiovascular diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is an important modulator of heart function, and can thus lead to lower activity and cardiac load, so that SD such as insomnia, sleeplessness and hypersomnia have also been considered as important factors in the pathogenesis and progression of cardiovascular diseases [9]. Cardiovascular disease is the most common cause of death and disability in the world and in Iran.…”
Section: Introductionmentioning
confidence: 99%